Pengaruh Penerapan Metode Inkuiri terhadap Hasil Belajar Matematika Siswa Pada Materi Luas Permukaan Tabung di Kelas IX SMP Negeri 1 Muara Telang - Febriyati, Vivi; Siroj, Rusdy A; Supriadi, Agus (Journal of Innovation in Teaching and Instructional Media, 2021)
The purpose of this study was to determine the extent of the influence of the Inquiry method on student mathematics learning outcomes on the tube surface area material in class IX SMP Negeri 1 Muara Telang. This type of research is experimental research using true experimental research design. The subjects in this study were class (experimental class) and class (control class) SMP Negeri 1 Muara Telang. Based on the data analysis, it was obtained that the learning outcomes of mathematics using the classroom inquiry method, totaling 31 students, received an average value and a standard deviation . While the results of learning mathematics using the class expository method, which amounted to 31 students got the average value and standard deviation . Based on the t-test statistic, it is found that and with the degree of freedom and this significant level it means that it lies in the area of ​​rejection which means t is accepted. So, it can be concluded that the application of the inquiry method is more influential than the expository method on student mathematics learning outcomes on the tube surface area material in class IX SMP Negeri 1 Muara Telang.